Thermodynamic and nutritional properties and drying kinetics of pequi (Caryocar brasiliense Cambess) mesocarp - Jéssica L. F. Souza; Daniel E. C. Oliveira; Geovana R. Plácido; Mariana B. Egea; Márcio Caliari; Marco A. P. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objectives of this study were to fit mathematical models to the experimental data of the drying of the pequi mesocarp, determine the effective diffusion coefficient, and to obtain activation energy and thermodynamic and nutritional properties in different drying conditions. The mesocarp of pequi fruits, with an initial moisture content of 5.05 (decimal, dry basis), was dried in a forced ventilation oven at temperatures of 40, 50, 60 and 70 °C until the final moisture content of 0.15 ± 0.01 (decimal, dry basis). The mathematical models were adjusted by non-linear regression analysis using the Gauss-Newton method, considering the magnitude of the coefficient of determination (R2), the mean relative error (P) and the estimated mean error (SE). Among the models analyzed, the Midilli model presented the best fit. The effective diffusion coefficient increased with increase in temperature, and the activation energy on drying was 11.011 kJ mol-1. The enthalpy decreased with an increase in the drying temperature, while the entropy and Gibbs free energy increased with the drying temperature. The product obtained from drying has low lipid and high carbohydrate concentration, while temperatures above 70 °C could cause denaturation and/or protein complexation. The temperature of 60 °C is most suitable to obtain flour of pequi mesocarp, due to the shorter processing time while maintaining the nutritional quality.